Experimental and theoretical study of urban tree instantaneous and hourly transpiration rates and their cooling effect in hot and humid area. (May 2021) - Zheng, Senlin; Guldmann, Jean-Michel; Wang, Zhangyuan; Qiu, Zining; He, Caiwei; Wang, Kailai
Highlights: Transpiration rate (Tr) of four trees were obtained by field measurements. Tr of the four trees range from 18 to 54 mg m −2 s −1, with 229 W/m 2 energy loss. A theoretical model of predicting trees Tr is proposed, and its accuracy is verified. Predictability of trees Tr is improved (RMSE from 40 to 5.7 mg/m 2 s). On average, 33.2 % of incoming solar radiation is converted into latent heat. Abstract: The transpiration of trees is an important factor in the surface energy balance and the hydrosphere-atmosphere-biosphere water vapor cycle. It is also the main cause of a tree's ecological effects, such as cooling and humidification. A major challenge is to establish a model that can accurately predict the transpiration rate of urban trees at different time scales. To address this challenge, field measurements are used to obtain the instantaneous and hourly transpiration rates of four common subtropical trees ( Bauhinia blakeana, Mangifera indica, Ficus microcarpa and Michelia alba ), and their cooling effects are analyzed. The transpiration rate for the four trees ranges from 18 to 54 mg m −2 s −1, and the estimated energy loss due to transpiration ranges from 178 to 274 W/m 2, with an average of 229 W/m 2 . On average, 33.2 % of incoming solar radiation is converted into latent heat. The Shuttleworth-Wallace model, including canopy resistance and soil resistance parameters, is adapted to urban tree characteristics in built-up environments. The resulting model is a theoretical model that provides a new methodology and reasonable results for predicting an urban tree's transpiration rate under urban conditions. Its accuracy at different time scales is verified with field measurements. The predictability of water vapor cycle, thermal comfort and surface energy budgets in urban environments will be enhanced by incorporating the transpiration model into urban canopy model. Future applications and development of this model will help provide guidelines for sustainable urban planning and urban landscape management in terms of water vapor cycle and heat island mitigation.